Determinants of new product development speed in China: A strategy tripod perspective. (August 2021) - Bao, Yongchuan; Su, Zhongfeng; Noble, Charles H.
Abstract: This research considers an increasingly critical strategy in business success – new product development (NPD) speed. While the determinants of NPD speed have received prior attention in the context of developed countries, we consider the important role of institutional factors that are unique to an emerging economy. Based on the strategy tripod perspective, we develop a conceptual model that examines the influences of institutions (legal inefficiency and government support), and the interplay of institutions, firm capability (absorptive capacity), and task environment (technological turbulence). An empirical study among 249 manufacturing firms in the largest emerging economy (China) provides strong support for the conceptual model. We find that both legal inefficiency and government support increase NPD speed, whereas absorptive capacity weakens the effect of legal inefficiency but enhances the effect of government support. Furthermore, technological turbulence reduces the negative interaction effect and the positive interaction effect of absorptive capacity with legal inefficiency and government support, respectively. This paper extends several research streams and offers useful recommendations to both managers and policy makers in an emerging economy. Highlights: Both legal inefficiency and government support drive NPD speed in China. Absorptive capacity weakens the effect of legal inefficiency but enhances the effect of government support. Technological turbulence reduces the interaction effects of absorptive capacity with legal inefficiency and government support.